Neural Interactome: Interactive Simulation of a Neuronal System - Kim, Jimin; Leahy, William; Shlizerman, Eli (Frontiers in Computational Neuroscience, 2019)
Both connectivity and biophysical processes determine the functionality of neuronal networks. We, therefore, develop a real-time framework, called Neural Interactome ,2, to simultaneously visualize and interact with the structure and dynamics of such networks. Neural Interactome is a cross-platform framework, which combines graph visualization with the simulation of neural dynamics, or experimentally recorded multi neural time series, to allow application of stimuli to neurons to examine network responses. In addition, Neural Interactome supports structural changes, such as disconnection of neurons from the network (ablation feature), as typically done in experiments. Neural dynamics can be explored on a single neuron level (using a zoom feature), back in time (using a review feature) and recorded (using presets feature). We implement the framework using a model of the nervous system of Caenorhabditis elegans (C. elegans) nematode, a model organism for which full connectome and neural dynamics have been resolved. We show that Neural Interactome assists in studying neural response patterns associated with locomotion and other stimuli. In particular, we demonstrate how stimulation and ablation help in identifying neurons that shape particular dynamics. We examine scenarios that were experimentally studied, such as touch response circuit, and explore new scenarios that did not undergo elaborate experimental studies. The development of the Neural Interactome was guided by generic concepts to be applicable to neuronal networks with different neural connectivity and dynamics.